Comparing National Stereotypes in different cultures: German in Dutch and Russian language teaching at schools and universities - Boonen, Ute K.; Wesche, Jörg; Awater, Pia (Glottodidactica, 2022)
Stereotypes, prejudices, hostile images and clichés are different forms of self-images and images of others. This paper establishes stereotypes as a scalable concept to distinguish them from other forms of fixed attributions. It features a comparison of national stereotypes about Germany, the Germans and the German language from a Dutch and Russian perspective and discusses the use of stereotypes in foreign language teaching, which are aimed at culturally reflective learning.